Theological Libraries in the UK and Ireland (Atla Open Press, 2026)
Marking the 70th Anniversary of the Association of British Theological and Philosophical Libraries (ABTAPL), librarians from across the United Kingdom and Ireland offer their perspectives on the past, present, and future of theological libraries and this organization. The book explores the history of ABTAPL, including its publications, membership, and meetings, as well as the development of libraries from different faith traditions across the United Kingdom and Ireland. Librarians provide insight into the challenges and opportunities found in managing theological libraries in unique contexts and explain the value of ABTAPL in providing connection and collaboration. This celebration of ABTAPL’s seven decades of achievements invites readers to look towards the future of the organization and find new ways to engage with their fellow librarians in the current era.